Effect of ZIP2 Gln/Arg/Leu (rs2234632) polymorphism on zinc homeostasis and inflammatory response following zinc supplementation. (8th December 2015) - Giacconi, Robertina; Costarelli, Laura; Malavolta, Marco; Cardelli, Maurizio; Galeazzi, Roberta; Piacenza, Francesco; Gasparini, Nazzarena; Basso, Andrea; Mariani, Erminia; Fulop, Tamas; Rink, Lothar; Dedoussis, George; et al.
Abstract: Zinc dyshomeostasis may lead to an augmented production of proinflammatory cytokines promoting chronic inflammation and increasing the susceptibility to age‐related diseases. Several studies suggest that the zinc transporter protein ZIP2 may play a relevant role in the immune system especially during zinc deficiency, while a polymorphism on the coding region of ZIP2 gene (Gln/Arg/Leu) has been associated with severe carotid artery disease. The aim of this study is to investigate the role of ZIP2 SNP on zinc and inflammatory status in 1090 elderly healthy free‐living subjects enrolled in the ZincAge project and to assess the effect of zinc supplementation on zinc status, inflammatory mediators, and zinc transporter expression depending on ZIP2 genotype. ZIP2 Leu− (Arg43Arg) carriers showed enhanced IL‐6, TNF‐α, and RANTES plasma levels associated with decreased free cytosolic zinc in PBMCs and an upregulation of zinc transporters ZIP2, ZIP8, and Znt1. Moreover, Leu− subjects displayed significant decrement of inflammatory mediators such as MCP‐1, TNF‐α, and RANTES following zinc supplementation. In summary, this investigation provides new evidence on the effect of ZIP2 Gln/Arg/Leu polymorphism on proinflammatory mediators and zinc homeostasis in elderly population with a more pronounced anti‐inflammatory effect of zinc supplementation in subjects carrying ZIP2 Leu− (Arg43Arg) genotype. These novel findings could be useful in identifying elderly subjects who may benefit of zinc intervention to decrease the inflammatory status and to prevent or delay the development of age‐related diseases. © 2015 BioFactors, 41(6):414–423, 2015